CAR-NK Cells: From Natural Basis to Design for Kill - Khawar, Muhammad Babar; Sun, Haibo (Frontiers in Immunology, 2021)
Chimeric antigen receptors (CARs) are fusion proteins with an extracellular antigen recognition domain and numerous intracellular signaling domains that have been genetically modified. CAR-engineered T lymphocyte-based therapies have shown great success against blood cancers; however, potential fatal toxicity, such as in cytokine release syndrome, and high costs are some shortcomings that limit the clinical application of CAR-engineered T lymphocytes and remain to overcome. Natural killer (NK) cells are the focal point of current immunological research owing to their receptors that prove to be promising immunotherapeutic candidates for treating cancer. However, to date, manipulation of NK cells to treat malignancies has been moderately successful. Recent progress in the biology of NK cell receptors has greatly transformed our understanding of how NK cells recognize and kill tumor and infected cells. CAR-NK cells may serve as an alternative candidate for retargeting cancer because of their unique recognition mechanisms, powerful cytotoxic effects especially on cancer cells in both CAR-dependent and CAR-independent manners and clinical safety. Moreover, NK cells can serve as an ‘off-the-shelf product’ because NK cells from allogeneic sources can also be used in immunotherapies owing to their reduced risk of alloreactivity. Although ongoing fundamental research is in the beginning stages, this review provides an overview of recent developments implemented to design CAR constructs to stimulate NK activation and manipulate NK receptors for improving the efficiency of immunotherapy against cancer, summarizes the preclinical and clinical advances of CAR-NK cells against both hematological malignancies and solid tumors and confronts current challenges and obstacles of their applications. In addition, this review provides insights into prospective novel approaches that further enhance the efficiency of CAR-NK therapies and highlights potential questions that require to be addressed in the future.